Methanol poisoning in South- South Nigeria: Reflections on the outbreak response - Nnanna Onyekwere; Ifeoma Nwadiuto; Sylvester Maleghemi; Omosivie Maduka; Tamuno-Wari Numbere; Ndubuisi Akpuh; Esther Kanu; Ifeoma Katchy; Ibitein Okeafor (AOSIS, 2018)
The methanol poisoning outbreak in Rivers State in May 2015, involved 84 persons in five local government areas. An incident management system comprised of an Emergency Preparedness and Response (EPR) committee and the Local Government Area Rapid Response Teams in an Emergency Operations Centre (EOC). The EOC teams conducted case finding activities, line listing, and descriptive analysis, a retrospective cohort study and collection of local gin samples for laboratory investigation. They also coordinated community mobilization and sensitization activities, intervention meetings with local gin sellers, trace back activities and case management. Those affected were male (72; 85.7%) aged between 20 and 79 years. Of the 55 persons whose socio-demographics were obtained, forty-one persons (74.6%) were married, and 23 (41.8%) had primary education. Case fatality rate was 83.3% with an attack rate of 16 per 100,000 persons. Those exposed to ingestion of adulterated gin were six times more likely to develop methanol poisoning than those not exposed RR=6 (1.0-38.5); P=0.0078. It is hoped that this experience has positioned the state for better preparedness towards future outbreaks.